2013
DOI: 10.2478/prolas-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Genetic Resources of Some Legume Species of Latvian Origin by Plant Tissue Culture

Abstract: Accessions with no germinating seeds are a common problem in plant gene banks and research institutions. Our goal was to elaborate and apply an in vitro method of germination and multiplication of old aged seeds of red and alsike clover and alfalfa. Eighteen clover and five alfalfa accessions were used for germination in vitro. Most of the accessions had produced seeds more than 20 years ago and the seeds did not germinate in soil. Seed pre-treatment with different concentrations of potassium permanganate, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Potassium permanganate has oxidizing properties and can act as ethylene neutralizer or an antiseptic. It helped in germination of some legume seeds stored for 20 -44 years (Grauda et al, 2013). It is found that on-farm' seed priming with KH 2 PO 4 improved fertilizer-use efficiency and increased yield and profit for different crops grown on Pdeficient soils (Ali et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium permanganate has oxidizing properties and can act as ethylene neutralizer or an antiseptic. It helped in germination of some legume seeds stored for 20 -44 years (Grauda et al, 2013). It is found that on-farm' seed priming with KH 2 PO 4 improved fertilizer-use efficiency and increased yield and profit for different crops grown on Pdeficient soils (Ali et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium permanganate has oxidizing properties and can act as ethylene neutralizer or an antiseptic. It helped in germination of some legume seeds stored for 20 -44 years [13]. It is found that on-farm' seed priming with KH2PO4 improved fertilizer-use efficiency and increased yield and profit for different crops grown on P deficient soils [14].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium permanganate has oxidizing properties and can act as ethylene neutralizer or an antiseptic. It helped in germination of some legume seeds stored for 20 -44 years (Grauda et al, 2013). Hence, an attempt was made to examine the feasibility of modifying the storage atmosphere for freshly extracted seeds, to reduce respiration rates, leading to prolonged quality retention.…”
Section: Introductionmentioning
confidence: 99%